Antiproliferative effect of wild berries and North-Eastern Siberian bulbous spleen carp on breast cancer cells MCF-7 - A. N. Egorov; D. G. Tikhonov; A. S. Golderova (Успехи молекулярной онкологии, 2024)
Introduction. Studies have shown that natural compounds from various plants including berries can have antitumor activity. We examined Phlojodicarpus sibiricus extract as well as homogenates of wild berries such as hawthorn, cranberry, brier; all these plants contain a variety of biologically active compounds: flavonoids, carotenoids, anthocyanins and other polyphenols.Aim. To evaluate cytotoxicity of wild berries and Phlojodicarpus sibiricus growing in Northwestern Siberia in Michigan Cancer Foundation-7 (MCF-7) breast cancer cell line using the МТТ assay.Materials and methods. We examined homogenates of wild berries including Dahurian hawthorn (Crataegus dahurica Koehne), bog cranberry (Oxycoccus microcarpus Turcz.), Yakut brier (Rosa jacutica Juz.) and extract of the above-ground part (leaves, stems) of Phlojodicarpus sibiricus. Cytotoxicity of the prepared homogenates was evaluated on the MCF-7 cell line. For homogenate screening, colorimetric assay for assessing cell metabolic activity МТТ was used.Results. Dahurian hawthorn, bog cranberry and Yakut brier have statistically significant cytotoxic effect on tumor cells at concentration of 100 mg/mL in incubation medium. Among the evaluated berries, Yakut brier demonstrated the highest suppression of MCF-7 cell line growth: at dose 100 mg/mL it decreased it by 80.19 % compared to control. Extract of Phlojodicarpus sibiricus at concentration 10 mg/mL left only 4.95 % of the MCF-7 cells alive.Conclusion. Therefore, wild berries have antiproliferative potential. Being edible, they can be helpful in prevention of oncological diseases. High antiproliferative activity of Phlojodicarpus sibiricus demonstrated by us in this and previous studies indicate that it can be considered a source of effective antitumor compounds.